What’s the Beef with Consumer Appeal? - Kelli G. Garrett (Kansas Agricultural Experiment Station Research Reports, 2026)
Objective: The objective of this study was to determine the specific color consumers most prefer as the appealing bright, cherry-red beef color. Study Description: Color samples were created from an original hexadecimal score that was assumed to be the ideal bright, cherry-red beef color, with variations to reflect beef colors consumers may encounter in retail. A 5 × 5 grid was generated from this hex: darker tones extended left, brighter shades upward, lighter hues right, and duller tones downward. Each trait (darkness, brightness, lightness, dullness) included two adaptations, producing nine base color squares. From these nine, four additional hexes were developed by combining two traits within each quadrant. Consumers (n = 192) then completed a survey with 10 randomly selected samples, rating their overall liking and indicating whether they would purchase beef steaks of that color. The Bottom Line: Consumers prefer moderately light and bright shades of beef color over darker hues. As beef color becomes darker, consumers become more critical regardless of brightness.
Keywords: red; beef; color